Pengaruh Stretching Terhadap Kelelahan Kerja Pada Pekerja Garmen di PT CI Karanganyar - Imanugraha, Dhiaulhaq Bagus; Setyawan, Haris; Chahyadhi, Bachtiar (STIKES Ngesti Waluyo, 2024)
Work fatigue can negatively impact the productivity, well-being, and safety of workers in the industry. The garment industry, known for its high workload, tight time demands, and ambitious production schedules, often exposes workers to an increased fatigue risk. This study aims to determine the effect of stretching on work fatigue in garment workers at PT CI Karanganyar. This quasi-experimental study employed a pre-test and post-test with a control group design. The study involved 40 production workers in the garment work section at PT CI Karanganyar, with 20 workers assigned to the intervention and other 20 workers to the control groups. Work fatigue was measured using the Subjective Self-Rating Test questionnaire. The analysis of the results using the Paired Sample T-Test showed that the p-value was <0.001 in the experimental group, while in the control group, it was 0.097. The Independent Sample T-Test analysis revealed a p-value of 0.015. These findings suggest that stretching has a significant effect on reducing work fatigue among production workers at PT CI Karanganyar.